Seven ways to get a grip on implementing Competency-Based Medical Education at the program level - Dagnone, Jeffery Damon; McEwen, Laura; Taylor, David; Acker, Amy; Bouchard, Mary; DeJong, Peggy; Chamberlain, Susan; Dos-Santos, Andrew; Fleming, Melinda; Hall, Andrew; Jaeger, Melanie; Mann, Steve; et al. (Canadian Medical Education Journal, 2020)
Competency-based medical education (CBME) curricula are becoming increasingly common in graduate medical education. Put simply, CBME is focused on educational outcomes, is independent of methods and time, and is composed of achievable competencies.1 In spite of widespread uptake, there remains much to learn about implementing CBME at the program level. Leveraging the collective experience of program leaders at Queen’s University, where CBME simultaneously launched across 29 specialty programs in 2017, this paper leverages change management theory to provide a short summary of how program leaders can navigate the successful preparation, launch, and initial implementation of CBME within their residency programs.